The Impact of Social Media on Medical Professionalism: A Systematic Qualitative Review of Challenges and Opportunities - Gholami-Kordkheili, Fatemeh; Wild, Verina; Strech, Daniel (JMIR Publications, 2013)
BackgroundThe rising impact of social media on the private and working lives of health care professionals has made researchers and health care institutions study and rethink the concept and content of medical professionalism in the digital age. In the last decade, several specific policies, original research studies, and comments have been published on the responsible use of social media by health care professionals. However, there is no systematic literature review that analyzes the full spectrum of (1) social media-related challenges imposed on medical professionalism and (2) social media-related opportunities to both undermine and improve medical professionalism. ObjectiveThe aim of this systematic qualitative review is to present this full spectrum of social media-related challenges and opportunities. MethodsWe performed a systematic literature search in PubMed (restricted to English and German literature published between 2002 and 2011) for papers that address social media-related challenges and opportunities for medical professionalism. To operationalize "medical professionalism", we refer to the 10 commitments presented in the physicians' charter "Medical professionalism in the new millennium" published by the ABIM Foundation. We applied qualitative text analysis to categorize the spectrum of social media-related challenges and opportunities for medical professionalism. ResultsThe literature review retrieved 108 references, consisting of 46 original research studies and 62 commentaries, editorials, or opinion papers. All references together mentioned a spectrum of 23 broad and 12 further-specified, narrow categories for social media-related opportunities (n=10) and challenges (n=13) for medical professionalism, grouped under the 10 commitments of the physicians' charter. ConclusionsThe accommodation of the traditional core values of medicine to the characteristics of social media presents opportunities as well as challenges for medical professionalism. As a profession that is entitled to self-regulation, health care professionals should proactively approach these challenges and seize the opportunities. There should be room to foster interprofessional and intergenerational dialogue (and eventually guidelines and policies) on both challenges and opportunities of social media in modern health care. This review builds a unique source of information that can inform further research and policy development in this regard.